2017
DOI: 10.1098/rstb.2016.0469
|View full text |Cite
|
Sign up to set email alerts
|

Connecting theory and data to understand recombination rate evolution

Abstract: Meiotic recombination is necessary for successful gametogenesis in most sexually reproducing organisms and is a fundamental genomic parameter, influencing the efficacy of selection and the fate of new mutations. The molecular and evolutionary functions of recombination should impose strong selective constraints on the range of recombination rates. Yet, variation in recombination rate is observed on a variety of genomic and evolutionary scales. In the past decade, empirical studies have described variation in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 166 publications
(258 reference statements)
2
72
0
Order By: Relevance
“…A third possibility is that recombination itself is frequently subject to directional selection (Segura et al. ; Dapper and Payseur ; Ritz et al. ), driving divergence at the underlying genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A third possibility is that recombination itself is frequently subject to directional selection (Segura et al. ; Dapper and Payseur ; Ritz et al. ), driving divergence at the underlying genes.…”
Section: Discussionmentioning
confidence: 99%
“…). Despite important insights about the conditions that favor recombination rate evolution from theoretical work, the balance of evolutionary forces responsible for observed patterns of inter‐individual variation in nature has rarely been examined (Dapper and Payseur ; Ritz et al. ).…”
Section: List Of 32 Genes Surveyed Organized By Step In the Recombinmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the number of recombination events (crossovers) per genome (recombination rate) and their distribution along the chromosomes are considered as important genomic characteristics of species and studied actively in plants, fungi and animals (mostly mammals). These studies demonstrated substantial interspecies variation in recombination rate (Dumont and Payseur 2008;Frohlich et al 2015;Dapper and Payseur 2017;Stapley et al 2017) while withinpopulation variation was found to be of the same magnitude across various taxa (Ritz et al 2017). The minimum possible rate of recombination is constrained by the necessity of at least one crossover per pair of homologous chromosomes to ensure their orderly segregation in the first meiotic division.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the total genome size and the total length of the synaptonemal complex (SC, the core structure of pachytene chromosomes) may also serve as predictors of species-specific recombination rate (Peterson et al 1994;Kleckner et al 2003). While molecular and cellular mechanisms controlling the recombination rate are more or less clear, the adaptive importance of interspecies differences for this trait remains a matter of discussion (Stapley et al 2017;Dapper and Payseur 2017;Ritz et al 2017).…”
Section: Introductionmentioning
confidence: 99%